Methods of estimating the state of the mechanisms of regulation of cardiac activity for girls 9-10 years of age during physical training aimed at developing endurance - Samokih I.I (Kharkov National Pedagogical University, 2012)
Are considered indicators of regulation of cardiac activity proposed D.N. Davidenko et al. (1984). It is established age-related indicators in girls from 9 to 10 years. It is shown that in the process of double-entry physical training with the implementation of priority endurance exercise significantly improves the efficiency of regulation of cardiac activity for girls. The expediency of the lessons of physical culture directed on the priority of development endurance to improve the physical health of school girls of primary school.